Fan blade damping boss wear-resistant layer assembly and pulse current diffusion welding preparation method thereof

CN122875897APending Publication Date: 2026-10-09TAIHANG LABORATORY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611391617.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种风扇叶片减震凸台耐磨层组件及其脉冲电流扩散焊制备方法,以解决传统钎焊工艺界面结合强度低、脆性相多、热损伤大的技术问题

Benefits of technology

[0018]与现有技术相比,本说明书实施例采用的上述至少一个技术方案能够达到的有益效果至少包括:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875897A_ABST
    Figure CN122875897A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of aero-engine manufacturing, and provides a fan blade shock-absorbing boss wear-resistant layer assembly and a pulse current diffusion welding preparation method thereof, which comprises the following steps: processing WC-Co hard alloy into a suitable wear-resistant block; using a discharge plasma sintering technology to press a titanium-based filler powder into a filler pre-sintered sheet; and performing pulse current diffusion welding under the process condition of forming a continuous liquid phase film of the pre-sintered sheet, so as to realize metallurgical bonding. The obtained assembly has a gradient diffusion layer with a thickness of 8 microns to 15 microns between the wear-resistant block and the shock-absorbing boss, Ti elements at the interface are distributed in a decreasing gradient, and the interface contains a continuous and dense TiC and / or ZrC reaction layer. Through the synergistic effect of the pre-sintered sheet and the pulse current, the application effectively solves the problem of large brittleness and low bonding strength of a traditional brazing interface, and meets the long-life service requirement of an aero-engine fan blade.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aero-engine manufacturing technology and relates to a wear-resistant layer assembly for a fan blade vibration damping boss and its preparation method by pulsed current diffusion welding. Background Technology

[0002] Fan blades are key rotating components in turbine machinery such as aero engines, playing a crucial role in delivering air into the internal flow channels of the machine. During operation, the blades are subjected to significant centrifugal, aerodynamic, thermal, and vibrational loads, making them prone to failure. To address vibration issues, fan blades typically utilize the Coulomb friction damping principle, incorporating damping structures (such as damping bosses) on the blade body to increase the clamping rigidity at both ends of the blade and raise its natural frequency. Simultaneously, during vibration, the working surfaces of the damping structures rub against each other to absorb vibrational energy, which also helps suppress flutter.

[0003] Currently, vacuum high-frequency induction brazing is commonly used in the manufacturing and repair of fan blades in China to prepare a wear-resistant layer on the working surface of the damping and vibration-damping structure (protrusion). The specific process is as follows: First, a titanium-based paste-like brazing filler metal mixed with tungsten carbide wear-resistant particles is coated onto the blade damping and vibration-damping interface. The brazing filler metal is then melted by induction heating, causing the wear-resistant particles to be welded to the interface surface. The entire process involves more than ten steps, including grinding, mixing, welding the protective strip, applying the brazing filler metal, brazing, removing the protective strip, and grinding and polishing.

[0004] However, existing processes for preparing wear-resistant layers for bosses have the following prominent problems: First, the wear-resistant layer has a short service life. The entire wear-resistant layer is a mixture of brazing filler metal and tungsten carbide particles, with about half of the contact interface being the brazing filler metal matrix, which has poor wear resistance, resulting in insufficient overall wear resistance. Second, the wear-resistant layer has poor quality stability. The wear-resistant particles are unevenly distributed and tend to deposit in the bottom area. Furthermore, the binder in the mixed brazing filler metal vaporizes and volatilizes at high temperatures, causing welding pores to form inside the wear-resistant layer and reducing its density, which seriously affects its mechanical properties. Third, the process is lengthy and requires high process control. The brazing filler metal and wear-resistant particles are only effective for 16 to 24 hours after mixing. The quality of mixing, coating, and brazing is extremely dependent on the operator's skill level and work experience, making it difficult to guarantee batch production consistency.

[0005] Therefore, there is an urgent need to develop a wear-resistant layer component that can obtain a high-strength, low-damage interface and a new method for its preparation. Summary of the Invention

[0006] The purpose of this invention is to provide a wear-resistant layer assembly for a fan blade damping boss and its preparation method by pulsed current diffusion welding, so as to solve the technical problems of low interface bonding strength, multiple brittle phases, and large thermal damage in traditional brazing processes.

[0007] Specifically, the technical solution for achieving the objective of this invention is as follows:

[0008] In a first aspect, the present invention discloses a pulsed current diffusion welding method for preparing a wear-resistant layer assembly for a fan blade vibration damping boss, the method comprising the following steps: S1. The WC-Co cemented carbide is machined into a wear-resistant block that is compatible with the working surface of the fan blade damping boss. S2. Titanium-based brazing filler powder is pressed into brazing filler pre-sintered sheets using spark plasma sintering technology. The densification degree of the brazing filler pre-sintered sheets meets the requirements for forming a continuous liquid phase film during subsequent pulsed current diffusion welding. S3. Stack the brazing pre-sintered sheet between the working surface of the fan blade damping boss and the wear-resistant block and fix it to form a component to be welded; S4. Place the component to be welded in a pulsed current diffusion welding device, and perform pulsed current diffusion welding under the process conditions that make the brazing filler metal pre-sintered sheet form a continuous liquid phase film, so that the wear-resistant block is metallurgically bonded to the fan blade damping boss through the brazing filler metal pre-sintered sheet, and obtain the fan blade damping boss wear-resistant layer component.

[0009] Further, in step S2, the titanium-based solder powder is Ti-Zr-Cu-Ni or Ti-Cu-Ni, and the density of the solder pre-sintered sheet is 96%~99.5%.

[0010] Furthermore, the density of the brazing filler metal pre-sintered sheet is ≥98%, and the average grain size is ≤5μm.

[0011] Furthermore, in step S2, the temperature of the spark plasma sintering is 750℃~850℃, the axial pressure is 30MPa~50MPa, and the holding time is 3min~10min.

[0012] Further, in step S4, the process conditions satisfy any of the following combinations: (1) The welding temperature is 750℃~850℃ and the welding time is 30min~90min; (2) The welding temperature is 850℃~950℃, and the welding time is 20min~45min; The welding temperature is negatively correlated with the welding time, and the welding time is 30 min to 45 min at 850℃.

[0013] Further, in step S1, the WC-Co cemented carbide is WC-10Co or WC-12Co, the thickness of the wear-resistant block is 500μm~1000μm, and the surface roughness Ra of the mating surface is ≤0.4μm.

[0014] Further, in step S3, the thickness of the pre-sintered brazing filler metal sheet is 50μm~250μm, the area is not less than the contact surface area of ​​the wear-resistant block, and the difference in thermal expansion coefficient between it and the WC-Co cemented carbide is ≤2×10. -6 / ℃.

[0015] Secondly, this invention discloses a wear-resistant layer assembly for a fan blade damping boss, prepared by the pulsed current diffusion welding method described in the first aspect above. A gradient diffusion layer with a thickness of 8μm~15μm is present between the wear-resistant block and the fan blade damping boss. The Ti element at the interface exhibits a decreasing gradient distribution, and the layer comprises a continuous and dense TiC and / or ZrC reaction layer. The average particle size of the compounds is ≤2μm, and the interfacial shear strength of the gradient diffusion layer is ≥265MPa.

[0016] Furthermore, the volume fraction of the TiC and / or ZrC reaction layer in the gradient diffusion layer is 15% to 30%.

[0017] Furthermore, the interfacial shear strength of the gradient diffusion layer is ≥265MPa, and the Co content within 50μm of the surface layer of the wear-resistant block after welding is reduced by no more than 5wt% compared to the original value.

[0018] Compared with the prior art, the beneficial effects that at least one technical solution adopted in the embodiments of this specification can achieve include at least: 1. High interfacial bonding strength: Pulsed current diffusion welding utilizes electroplasticity and electrodiffusion effects to activate the interface to be welded, promoting pore closure and directional diffusion of elements, achieving full spreading and wetting; the brazing filler metal pre-sintered sheet prepared by spark plasma sintering has high density (96%~99.5%) and fine grains (≤5μm), and its densification is sufficient to form a continuous liquid phase film during pulsed current diffusion welding, which fully closes the interfacial micropores under axial pressure. At the same time, C generated by WC decomposition reacts in situ with Ti / Zr to generate nano-sized TiC / ZrC particles, forming a gradient diffusion layer, so that the interfacial shear strength reaches more than 265MPa, which is significantly better than the 180MPa level of traditional brazing.

[0019] 2. Minimal thermal damage and excellent performance of the wear-resistant block: Compared to traditional processes, pulsed current diffusion welding can achieve a heating rate of 100℃ / min~200℃ / min, significantly shortening the welding time and reducing the thermal impact on the base material, effectively minimizing the loss of the Co binder phase in WC-Co cemented carbide. In the preferred embodiment, the Co content within the surface 50μm of the wear-resistant block after welding decreases by no more than 2.1wt% compared to the original value; in all other embodiments, this value does not exceed 5wt%, indicating that the process conditions of the present invention cause minimal thermal damage to the wear-resistant block, maintaining its original hardness and toughness and extending the service life of the wear-resistant layer.

[0020] 3. Clear process window and strong adaptability: Through extensive experimental verification, this invention has established a wide process window of 750℃~950℃ / 20min~90min and a wide density range of 96%~99.5%, as well as the negative correlation between welding temperature and welding time. A clear preferred range of 30min~45min is given at the 850℃ inflection point. By adjusting the brazing filler metal system and welding parameters, it can be adapted to fan blade damping bosses of different sizes and materials. It is especially suitable for large-size wear-resistant blocks and temperature-sensitive lightweight substrates, and has broad engineering application prospects.

[0021] 4. The product has stable performance and detectable structural features: the thickness of the gradient diffusion layer at the interface of the obtained component is controlled at 8μm~15μm, the average particle size of the compound is ≤2μm, the structure is uniform and dense, and there are no cracks or pores; the present invention also provides clear and feasible detection methods for each structural feature, which is convenient for third-party verification and rights protection evidence.

[0022] 5. Simplified process and good consistency: The use of prefabricated wear-resistant blocks and pre-sintered sheets to replace manual mixing and coating avoids the 16-24 hour shelf life limitation after the brazing filler metal and wear-resistant particles are mixed, reduces the dependence on the operator's skill level, facilitates standardized and refined mass production, and can be extended to the rapid repair application of aero-engines in the field. Attached Figure Description

[0023] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 This is a flowchart of the pulsed current diffusion welding preparation method for the wear-resistant layer assembly of the fan blade vibration damping boss of the present invention; Figure 2 This is a schematic diagram of the cross-sectional structure of the wear-resistant layer component of the fan blade damping boss of the present invention; Figure 3 This is a schematic diagram of the microstructure of the gradient diffusion layer of the present invention; Among them, 1. fan blade damping boss; 2. gradient diffusion layer; 3. wear-resistant block; 4. TiC / ZrC reaction layer; 5. brazing filler metal pre-sintered sheet. Detailed Implementation

[0025] The embodiments of this application will now be described in detail with reference to the accompanying drawings.

[0026] The following specific examples illustrate the implementation of this application. Those skilled in the art can easily understand other advantages and effects of this application from the content disclosed in this specification. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. This application can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of this application. It should be noted that, in the absence of conflict, the following embodiments and features of the embodiments can be combined with each other. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0027] To facilitate the detection and verification of the product structural features of the present invention, the detection methods for each structural feature are described below: Gradient diffusion layer thickness: The cross-section of the weld interface was observed by backscattered electron (BSE) imaging using a scanning electron microscope (SEM). The thickness of the diffusion reaction zone was measured along the vertical direction of the interface. At least 5 fields of view were randomly selected, and 3 positions were measured in each field of view. The arithmetic mean was taken as the final result.

[0028] Ti element gradient distribution: Energy dispersive X-ray spectroscopy (EDS) line scanning analysis was used, with the scanning direction perpendicular to the welding interface. The scan was performed continuously from the wear-resistant block side to the fan blade damping boss substrate side, with a step size of 0.5 μm. The atomic percentage of Ti element as a function of distance was collected, and its decreasing gradient distribution characteristics were observed.

[0029] TiC and / or ZrC reaction layer: Confirmed by SEM-BSE imaging combined with EDS elemental distribution analysis, the continuous and dense TiC and / or ZrC layer is characterized by a continuous and uninterrupted banded distribution near the WC-Co side in the gradient diffusion layer, without cracks or pores.

[0030] Average particle size of compounds: SEM-BSE image analysis was used. At least 5 fields of view were randomly selected in the gradient diffusion layer region, and the maximum size of no less than 20 compounds was measured in each field of view. The arithmetic mean was then taken.

[0031] Interfacial shear strength: The test was conducted in accordance with GB / T 6400-2007 "Metallic materials, wire and rivet, shear test method" or ASTM F1044-05 "Standard Test Method for Shear Testing of Calcium Phosphate Coatings and Metallic Coatings". Overlap shear specimens were used, and the loading rate was 1 mm / min. The shear strength value was obtained by dividing the fracture load by the joint area.

[0032] Interface porosity: SEM-BSE image analysis was used to perform image binarization on the welding interface area and calculate the percentage of the pore area to the total interface area. At least 5 fields of view were randomly selected and the average value was taken.

[0033] Co content: EDS point analysis or line scan analysis was used, and the measurement was carried out point by point from the surface of the wear-resistant block to the inside in a direction perpendicular to the interface, with a step size of 1μm. The test conditions were an accelerating voltage of 20kV and a working distance of 15mm. The arithmetic mean of at least 3 parallel scan lines was taken.

[0034] This invention provides a pulsed current diffusion welding method for preparing a wear-resistant layer assembly for a fan blade vibration damping boss, as shown in the embodiment of the invention. Figure 1 As shown, it includes the following steps: S1. The WC-Co cemented carbide is machined into a wear-resistant block that is compatible with the working surface of the fan blade damping boss.

[0035] In a preferred embodiment, the WC-Co cemented carbide is WC-10Co or WC-12Co, the thickness of the wear-resistant block is 500μm~1000μm, and the surface roughness Ra of the mating surface between the wear-resistant block and the fan blade damping boss is ≤0.4μm.

[0036] In a preferred embodiment, after step S1 and before step S2, the processed wear-resistant block can be subjected to plasma surface activation treatment to increase the surface energy of the wear-resistant block to ≥45mJ / m² and the surface oxygen content to ≤0.5wt%.

[0037] In a preferred embodiment, the wear-resistant block is formed by slow wire cutting and CNC grinding. After processing, the flatness of each surface of the wear-resistant block is ≤0.02mm, so that the absolute value of the dimensional tolerance is not greater than 0.1mm and not less than 0.02mm.

[0038] S2. Titanium-based brazing filler powder is pressed into brazing filler pre-sintered sheets using spark plasma sintering (SPS) technology. The densification degree of the brazing filler pre-sintered sheets is sufficient to form a continuous liquid phase film in subsequent pulsed current diffusion welding.

[0039] In this step, "sufficient densification to form a continuous liquid phase film" means that the density of the pre-sintered sheet is sufficient to form a continuous liquid phase film at the interface under pulsed current heating conditions. When the density is below 95%, there are a large number of interconnected pores inside the pre-sintered sheet, resulting in uneven current density distribution during pulsed current heating, preventing the liquid phase components from forming a continuous coverage, and causing large areas of unbonded regions at the welding interface. When the density reaches 96% or higher, the liquid phase film can form a continuous coverage in a relatively short time (usually ≤60s). In practice, the continuity of the liquid phase film can be verified by measuring the porosity of the welding interface to be ≤0.5%.

[0040] In a preferred embodiment, the density of the brazing filler metal pre-sintered sheet is 96% to 99.5%. The 96% to 98% range is suitable for cost-sensitive or large-size wear-resistant block applications. More preferably, the density of the brazing filler metal pre-sintered sheet is ≥98%, and the average grain size is ≤5μm. It should be noted that when used in high-reliability aero-engine components, this density requirement is ≥98%.

[0041] In a preferred embodiment, step S2 specifically includes: S21. Weigh Ti powder, Zr powder, Cu powder and Ni powder according to mass percentage and mix them evenly to obtain Ti-Zr-Cu-Ni titanium-based solder powder, or weigh Ti powder, Cu powder and Ni powder and mix them evenly to obtain Ti-Cu-Ni titanium-based solder powder, or weigh Ti powder, Ag powder, Cu powder and Ni powder and mix them evenly to obtain Ti-Ag-Cu-Ni titanium-based solder powder; S22. The titanium-based brazing filler powder is loaded into a graphite mold and pre-pressed to obtain a brazing filler blank; S23. Place the graphite mold containing the brazing filler blank into a spark plasma sintering furnace, and heat it to 750°C to 850°C at a heating rate of 50°C / min to 100°C / min under vacuum or inert atmosphere. Apply an axial pressure of 30MPa to 50MPa, hold for 3min to 10min, and then cool with the furnace to obtain the brazing filler pre-sintered sheet.

[0042] In a preferred embodiment, when the titanium-based solder powder is a Ti-Zr-Cu-Ni system, the mass percentage of each component is Ti 40%~50%, Zr 20%~30%, Cu 15%~25%, and Ni 5%~15%, preferably Ti 45%, Zr 25%, Cu 20%, and Ni 10%. When it is a Ti-Cu-Ni system, the mass percentage of each component is Ti 55%~65%, Cu 25%~35%, and Ni 5%~15%. When it is a Ti-Ag-Cu-Ni system, the mass percentage of each component is Ti 35%~45%, Ag 10%~20%, Cu 25%~35%, and Ni 5%~15%. The particle size of each of the Ti powder, Zr powder, Cu powder, Ni powder, and Ag powder is 200 mesh to 400 mesh.

[0043] In a preferred embodiment, the brazing filler metal pre-sintered sheet obtained in step S2 is surface-polished to remove oxide scale before use and wiped clean with anhydrous ethanol.

[0044] S3. The brazing filler metal pre-sintered sheet is stacked between the working surface of the fan blade damping boss and the wear-resistant block and fixed to form a component to be welded.

[0045] In a preferred embodiment, the thickness of the brazing filler metal pre-sintered sheet is 50μm~250μm, the area of ​​the brazing filler metal pre-sintered sheet is not less than the surface area of ​​the wear-resistant block facing the damping boss of the fan blade, and the difference between the thermal expansion coefficient of the brazing filler metal pre-sintered sheet and the thermal expansion coefficient of the WC-Co cemented carbide is ≤2×10. -6 / ℃.

[0046] S4. Place the component to be welded in a pulsed current diffusion welding device, and perform pulsed current diffusion welding under the process conditions that make the brazing filler metal pre-sintered sheet form a continuous liquid phase film, so that the wear-resistant block is metallurgically bonded to the fan blade damping boss through the brazing filler metal pre-sintered sheet, and the wear-resistant layer component of the fan blade damping boss is obtained.

[0047] In this step, the formation of a continuous liquid phase film can be confirmed by the interfacial porosity being ≤0.5% after welding, indicating that the liquid phase film has been fully spread and closed the interfacial micropores and voids during the welding process.

[0048] In a preferred embodiment, the process conditions satisfy any combination of the following: (1) The welding temperature is 750℃~850℃ and the welding time is 30min~90min; (2) The welding temperature is 850℃~950℃, and the welding time is 20min~45min; The welding temperature is negatively correlated with the welding time, and the welding time is 30 min to 45 min at 850℃.

[0049] The negative correlation between welding temperature and welding time means that as the welding temperature increases, the time required for the brazing filler metal pre-sintered sheet to form a continuous liquid phase film decreases. Simultaneously, to suppress excessive loss of the Co binder phase, the holding time in the high-temperature section needs to be reduced accordingly. Specifically, in the 750℃~850℃ range, the liquid phase film formation rate is slow, requiring 30min~90min to ensure sufficient interfacial reaction; in the 850℃~950℃ range, the liquid phase film forms rapidly, but Co diffusion intensifies, requiring the holding time to be controlled within 20min~45min. 850℃ is the process inflection point, at which point liquid phase film formation and Co loss reach dynamic equilibrium, corresponding to a holding time of 30min~45min.

[0050] In another preferred embodiment, the axial pressure of the pulsed current diffusion welding is 20MPa~40MPa, the duty cycle of the pulse current is 1:1~3:1, and the pulse frequency is 50Hz~10kHz; the welding interface temperature is monitored in real time during the heating process, and the deviation between the actual heating rate and the set heating rate is controlled to not exceed ±10℃ / min by adjusting the pulse current.

[0051] In this invention, to ensure welding quality, the Co content within the surface 50 μm of the wear-resistant block after welding is reduced by no more than 5 wt% compared to the original value. The Co content is determined using energy-dispersive X-ray spectroscopy (EDS) line scanning, with the scanning direction perpendicular to the interface, a step size of 1 μm, and 50 points collected for each line. The arithmetic mean of at least three parallel lines is taken as the final result. The original value refers to the baseline Co content measured under the same sample preparation, polishing, and EDS testing conditions as the welded sample, using WC-Co cemented carbide base material from the same batch that has not undergone any welding thermal cycling treatment.

[0052] In a preferred embodiment, after step S4 is completed, the process further includes: stress-relieving annealing of the welded fan blade damping boss wear-resistant layer assembly at a temperature of 500℃~600℃, holding for 1h~2h and then cooling with the furnace; then precision grinding of the working surface of the wear-resistant block to make its surface roughness Ra≤0.2μm and dimensional tolerance ±(0.02~0.05)mm, so as to obtain the final fan blade damping boss wear-resistant layer assembly.

[0053] This invention combines Figure 1 and Figure 2 The above method will be illustrated with the following specific examples: Example 1: Step 1: Select WC-10Co cemented carbide and process it into a wear-resistant block 3 with a thickness of 800μm by slow wire EDM and CNC grinding. After processing, the flatness of each surface is 0.015mm, the dimensional tolerance is ±0.05mm, and the surface roughness Ra=0.3μm of the mating surface. Then, the wear-resistant block 3 is subjected to plasma surface activation treatment. After treatment, the surface energy is 48mJ / m², and the surface oxygen content is 0.3wt%.

[0054] Step 2: Weigh out 45% Ti, 25% Zr, 20% Cu, and 10% Ni powder (all with a particle size of 300 mesh) by mass percentage, mix them evenly to obtain Ti-Zr-Cu-Ni titanium-based brazing filler powder; load the powder into a graphite mold to pre-press and form a brazing filler blank, place it in a spark plasma sintering furnace, heat it to 750℃ at 80℃ / min under vacuum conditions, apply an axial pressure of 40MPa, hold it at that temperature for 8min, and then cool it with the furnace to obtain a brazing filler pre-sintered sheet 5 with a density of 99.2% and an average grain size of 3.5μm; before use, grind the surface of the pre-sintered sheet to remove the oxide scale and wipe it clean with anhydrous ethanol. The densification degree of this pre-sintered sheet meets the conditions for forming a continuous liquid phase film in the subsequent pulsed current diffusion soldering.

[0055] Step 3: A pre-sintered brazing filler metal sheet 5, with a thickness of 150 μm and an area 1.05 times that of the contact surface of the wear-resistant block 3, is stacked between the working surface of the fan blade damping boss 1 and the wear-resistant block 3, and fixed with a graphite clamp to form the assembly to be welded; the difference in thermal expansion coefficient between the pre-sintered brazing filler metal sheet 5 and the WC-10Co cemented carbide is 1.2 × 10⁻⁶. -6 / ℃.

[0056] Step 4: Place the components to be soldered in the pulsed current diffusion soldering equipment and evacuate to a vacuum level of 3×10. -3 Pa, apply an initial pressure of 8MPa; apply a pulsed current (duty cycle 2:1, frequency 500Hz) at a heating rate of 150℃ / min to heat to 850℃, while simultaneously increasing the axial pressure to 30MPa at a linear rate; hold at 850℃ and 30MPa for 35min (within the preferred range of 30min~45min corresponding to 850℃) to allow the brazing filler metal to form an ultra-thin continuous liquid phase film with closed interface micropores, and allow C generated by WC decomposition to diffuse towards the brazing filler metal to generate a continuous and dense TiC / ZrC layer; stop the power supply, hold the pressure and cool to 350℃, then unload and remove the component; subsequently, perform stress-relief annealing on the welded component at 550℃ for 1.5h, and after furnace cooling, precisely grind the working surface of the wear-resistant block 3, achieving a final surface roughness Ra=0.15μm and a dimensional tolerance of ±(0.02~0.05)mm.

[0057] Testing revealed that the component prepared in this example exhibited a weld interface shear strength of 320 MPa, a gradient diffusion layer 2 thickness of 12 μm, a continuous and dense TiC / ZrC reaction layer 4, an average interfacial compound particle size of 1.5 μm, a TiC / ZrC reaction layer 4 volume fraction of 22% in the gradient diffusion layer 2, and a 2.1 wt% reduction in Co content within the 50 μm surface layer of the wear-resistant block 3 after welding compared to the original value. The interfacial porosity was 0.1%, meeting the requirements for installation on aero-engine fan blades.

[0058] Example 2: This example optimizes the process parameters based on Example 1 to improve the welding quality consistency of large-size wear-resistant blocks: Step 1: Select WC-12Co cemented carbide and process it into a wear-resistant block 3 with a thickness of 1000μm by slow wire EDM and CNC grinding. After processing, the flatness of each surface is 0.018mm, the dimensional tolerance is ±0.08mm, and the surface roughness Ra=0.35μm of the mating surface. Then, the wear-resistant block 3 is subjected to plasma surface activation treatment. After treatment, the surface energy is 52mJ / m², and the surface oxygen content is 0.2wt%.

[0059] Step 2: Weigh out Ti 48%, Zr 22%, Cu 20%, and Ni 10% powder (all with a particle size of 350 mesh) by mass percentage, mix them evenly to obtain Ti-Zr-Cu-Ni titanium-based solder powder; pre-press the powder into a graphite mold to obtain a solder blank, place it in a spark plasma sintering furnace, heat it to 780℃ at 60℃ / min under vacuum conditions, apply an axial pressure of 45MPa, hold it at that temperature for 10min, and then cool it with the furnace to obtain a solder pre-sintered sheet 5 with a density of 99.5% and an average grain size of 2.8μm; before use, grind the surface of the pre-sintered sheet to remove the oxide scale and wipe it clean with anhydrous ethanol. The densification degree of this pre-sintered sheet meets the conditions for forming a continuous liquid phase film in subsequent pulsed current diffusion soldering.

[0060] Step 3: Stack a 200μm thick brazing pre-sintered sheet 5, with an area 1.1 times the contact area of ​​the wear-resistant block 3, between the working surface of the fan blade damping boss 1 and the wear-resistant block 3, and fix it with a graphite clamp to form the assembly to be welded; the difference in thermal expansion coefficient between the brazing pre-sintered sheet 5 and the WC-12Co cemented carbide is 0.8×10. -6 / ℃.

[0061] Step 4: Place the components to be soldered in the pulsed current diffusion soldering equipment and evacuate to a vacuum level of 2×10⁻⁶. -3Apply an initial pressure of 10 MPa; apply a pulsed current (duty cycle 3:1, frequency 1 kHz) at a heating rate of 120 °C / min to heat to 880 °C, while simultaneously increasing the axial pressure to 35 MPa in stages (first increasing to 25 MPa at 20 MPa / min, holding for 2 min, then increasing to 35 MPa at 10 MPa / min); hold at 880 °C and 35 MPa for 25 min (falling to 850 °C~950 °C / 20 min). (Combined range of min~45min) to form an ultra-thin continuous liquid phase film closed interface micropores in the brazing filler metal, and C generated by WC decomposition diffuses towards the brazing filler metal side to generate a continuous and dense TiC / ZrC layer; stop the power supply, hold pressure and cool to 380℃, then unload and take out the component; then perform stress relief annealing on the welded component at 580℃×2h, and after furnace cooling, precision grind the working surface of wear-resistant block 3, with a final surface roughness Ra=0.12μm and dimensional tolerance ±(0.02~0.05)mm.

[0062] Testing revealed that the component prepared in this example exhibits a weld interface shear strength of 345 MPa, a gradient diffusion layer 2 thickness of 14 μm, a continuous and dense TiC / ZrC reaction layer 4 without cracks, an average particle size of 1.2 μm for the interface compounds, a volume fraction of 28% for the TiC / ZrC reaction layer 4 in the gradient diffusion layer 2, a 1.8 wt% reduction in Co content within the 50 μm surface layer of the wear-resistant block 3 after welding compared to the original value, and an interface porosity of 0.05%. This component is suitable for heavy-load conditions of high-thrust aero-engine fan blades.

[0063] Example 3: This example verifies the feasibility of the lower density limit boundary (96%~98%): Step 1: Select WC-10Co cemented carbide and process it into a wear-resistant block 3 with a thickness of 500μm by slow wire cutting and CNC grinding. After processing, the flatness of each surface is 0.012mm, the dimensional tolerance is ±0.03mm, and the surface roughness Ra=0.25μm of the mating surface. Then, the wear-resistant block 3 is subjected to plasma surface activation treatment. After treatment, the surface energy is 50mJ / m², and the surface oxygen content is 0.25wt%.

[0064] Step 2: Weigh out 40% Ti, 15% Ag, 30% Cu, and 15% Ni powder (all with a particle size of 400 mesh) by mass percentage, mix them evenly to obtain Ti-Ag-Cu-Ni titanium-based brazing filler powder; load the powder into a graphite mold for pre-pressing to obtain a brazing filler blank, place it in a spark plasma sintering furnace, heat it to 720℃ at 70℃ / min under vacuum conditions, apply an axial pressure of 35MPa, hold it at that temperature for 6min, and then cool it with the furnace to obtain a brazing filler pre-sintered sheet 5 with a density of 98.8% and an average grain size of 4.2μm. The density of this pre-sintered sheet is 96.5%, and its densification degree meets the conditions for forming a continuous liquid phase film in subsequent pulsed current diffusion soldering.

[0065] Step 3: Stack a pre-sintered brazing filler metal sheet 5 with a thickness of 80 μm and an area 1.02 times that of the contact surface of the wear-resistant block 3 between the working surface of the fan blade damping boss 1 and the wear-resistant block 3, and fix it with a graphite clamp to form the assembly to be welded; the difference in thermal expansion coefficient between the pre-sintered brazing filler metal sheet 5 and the WC-10Co cemented carbide is 1.5 × 10⁻⁶. -6 / ℃.

[0066] Step 4: Place the components to be soldered in the pulsed current diffusion soldering equipment and evacuate to a vacuum level of 4×10. -3 Pa, apply an initial pressure of 6MPa; apply a pulsed current (duty cycle 1:1, frequency 200Hz) at a heating rate of 180℃ / min to heat to 820℃, while simultaneously increasing the axial pressure to 25MPa at a linear rate; hold at 820℃ and 25MPa for 40min (falling within the range of 750℃~850℃ / 30min~90min) to form an ultrathin continuous liquid phase film with closed interface micropores in the brazing filler metal, and allow C generated by WC decomposition to diffuse towards the brazing filler metal side to generate a continuous and dense TiC layer; stop the power supply, hold the pressure and cool to 360℃, then unload and remove the component; subsequently, perform stress-relief annealing at 520℃ for 1h, and after furnace cooling, precisely grind the working surface of wear-resistant block 3, achieving a final surface roughness Ra=0.18μm and dimensional tolerance ±(0.02~0.05)mm.

[0067] Testing revealed that the component prepared in this example exhibited a welding interface shear strength of 295 MPa, a gradient diffusion layer 2 thickness of 9 μm, a continuous and dense TiC reaction layer 4, an average particle size of 1.8 μm for the interface compounds, a volume fraction of 18% for the TiC reaction layer 4 in the gradient diffusion layer 2, and a 2.5 wt% reduction in Co content within the surface 50 μm of the wear-resistant block 3 after welding compared to the original value. This meets the requirements for fretting wear resistance of the lightweight fan blade damping boss, and the substrate showed no significant thermal deformation during the welding process.

[0068] Example 4: This example verifies the feasibility of a 750℃ / 30min low-temperature short-time endpoint: Steps 1-3 are the same as in Example 3.

[0069] Step 4: Welding temperature 750℃, welding time 30min (falling to the lower limit of the combined range of 750℃~850℃ / 30min~90min), initial pressure 5MPa, heating rate 100℃ / min, axial pressure 20MPa, pulse current duty cycle 1:1, frequency 50Hz; unload after holding pressure and cooling to 400℃; annealing temperature 500℃×1h, surface roughness Ra=0.2μm after grinding, dimensional tolerance ±(0.02~0.05)mm.

[0070] Testing revealed that the component prepared in this example had a weld interface shear strength of 265 MPa, a gradient diffusion layer 2 thickness of 8 μm, a continuous TiC / ZrC reaction layer 4, an average particle size of 2.0 μm for the interface compounds, a volume fraction of 15% for the TiC / ZrC reaction layer 4 in the gradient diffusion layer 2, a Co content within 50 μm of the surface layer of the wear-resistant block 3 after welding that was 3.2 wt% lower than the original value, and an interface porosity of 0.4%. All indicators met the qualified standards.

[0071] Example 5: This example verifies the feasibility of a 950℃ / 20min high-temperature short-time endpoint: Step 1: Select WC-12Co cemented carbide and process it into a wear-resistant block 3 with a thickness of 600μm. The surface roughness Ra=0.38μm, the surface energy after surface activation treatment is 46mJ / m², and the surface oxygen content is 0.45wt%.

[0072] Step 2: Using a Ti-Cu-Ni solder (Ti 60%, Cu 30%, Ni 10%, particle size 250 mesh), the solder was sintered at 800℃ using SPS, with an axial pressure of 35MPa and a holding time of 5 minutes, resulting in a pre-sintered solder sheet 5 with a density of 98.5% and an average grain size of 4.5μm. The densification level of this pre-sintered sheet meets the requirements for forming a continuous liquid phase film in subsequent pulsed current diffusion soldering.

[0073] Step 3: The thickness of the brazing filler metal pre-sintered sheet 5 is 250 μm, and its area is 1.08 times that of the contact surface area of ​​the wear-resistant block 3. The difference in thermal expansion coefficient is 1.8 × 10⁻⁶. -6 / ℃.

[0074] Step 4: Welding temperature 950℃, welding time 20min (falling into the upper limit of the combination range of 850℃~950℃ / 20min~45min), initial pressure 7MPa, heating rate 130℃ / min, axial pressure 22MPa, pulse current duty cycle 2:1, frequency 80Hz; unload after holding pressure and cooling to 390℃; annealing temperature 530℃×1.5h, surface roughness Ra=0.19μm after grinding, dimensional tolerance ±(0.02~0.05)mm.

[0075] Testing revealed that the component prepared in this example had a weld interface shear strength of 280 MPa, a gradient diffusion layer 2 thickness of 10 μm, a continuous TiC reaction layer 4, an average particle size of 1.9 μm for the interface compounds, a volume fraction of 20% for the TiC reaction layer 4 in the gradient diffusion layer 2, and a Co content within the surface 50 μm of the wear-resistant block 3 after welding that was 4.1 wt% lower than the original value. The interface porosity was 0.2%. The performance was slightly lower than that of Examples 1-2, but still met the requirements for use.

[0076] Example 6: This example verifies the feasibility of a long-duration low-temperature endpoint at 750℃ / 90min: Steps 1-3 are the same as in Example 3.

[0077] Step 4: Welding temperature 750℃, welding time 90min, other parameters are the same as in Example 4.

[0078] Testing revealed that the component prepared in this example had a weld interface shear strength of 270 MPa, a gradient diffusion layer 2 thickness of 9 μm, a continuous TiC / ZrC reaction layer 4, an average particle size of 1.9 μm for the interface compounds, a TiC / ZrC reaction layer 4 volume fraction of 17% in the gradient diffusion layer 2, a Co content within the surface 50 μm of the wear-resistant block 3 after welding that was 3.5 wt% lower than the original value, and an interface porosity of 0.35%. All indicators met the qualified standards.

[0079] Example 7: This example verifies the feasibility of a high-temperature long-duration endpoint at 950℃ / 45min: Steps 1-3 are the same as in Example 5.

[0080] Step 4: Welding temperature 950℃, welding time 45min, other parameters are the same as in Example 5.

[0081] Testing revealed that the component prepared in this example had a weld interface shear strength of 268 MPa, a gradient diffusion layer 2 thickness of 10 μm, a continuous TiC reaction layer 4, an average particle size of 1.8 μm for the interface compounds, a TiC reaction layer 4 volume fraction of 19% in the gradient diffusion layer 2, a Co content within 50 μm of the surface layer of the wear-resistant block 3 after welding that was 4.8 wt% lower than the original value, and an interface porosity of 0.25%. All indicators met the qualified standards.

[0082] Example 8: This example verifies the feasibility of the upper limit endpoint of the 850℃ / 45min inflection point: Steps 1-3 are the same as in Example 1.

[0083] Step 4: Welding temperature 850℃, welding time 30min (at the lower limit of the preferred range of 30min~45min corresponding to 850℃), other parameters are the same as in Example 1.

[0084] Testing revealed that the component prepared in this example had a welding interface shear strength of 315 MPa, a gradient diffusion layer 2 thickness of 13 μm, a continuous and dense TiC / ZrC reaction layer 4, an average particle size of 1.4 μm for the interface compounds, a TiC / ZrC reaction layer 4 volume fraction of 24% in the gradient diffusion layer 2, a 2.5 wt% reduction in Co content within the surface 50 μm of the wear-resistant block 3 after welding compared to the original value, and an interface porosity of 0.08%.

[0085] Example 9: This example verifies the feasibility of conventional pretreatment (sampling + ultrasonic cleaning, omitting plasma activation): Step 1: Select WC-10Co cemented carbide and process it into a wear-resistant block 3 with a thickness of 800μm and a surface roughness Ra=0.3μm. Do not perform plasma surface activation treatment on the wear-resistant block. Only perform conventional grinding treatment (grinding with SiC sandpaper, 2.5μm diamond polishing agent and 0.5μm silica polishing agent in sequence) and ultrasonic cleaning with anhydrous ethanol for 15min, and then dry for later use.

[0086] Steps 2-3 are the same as in Example 1.

[0087] Step 4: Welding temperature 850℃, welding time 35min, other parameters are the same as in Example 1.

[0088] Testing revealed that the component prepared in this example exhibited a weld interface shear strength of 295 MPa, a gradient diffusion layer 2 thickness of 11 μm, a continuous and dense TiC / ZrC reaction layer 4, an average interfacial compound particle size of 1.6 μm, and a TiC / ZrC reaction layer 4 volume fraction of 20% in the gradient diffusion layer 2. After welding, the Co content within the surface 50 μm of the wear-resistant block 3 decreased by 2.3 wt% compared to the original value, and the interfacial porosity was 0.15%. This embodiment demonstrates that even without plasma surface activation treatment, conventional grinding and ultrasonic cleaning can still achieve weld quality that meets usage requirements. However, the shear strength is slightly lower than that of Example 1 (320 MPa) after plasma activation, indicating that plasma activation can further enhance interfacial bonding strength.

[0089] The present invention characterizes the interface microstructure of the fan blade damping boss wear-resistant layer components prepared in Examples 1-9: The components prepared in Example 1, such as Figure 3 As shown, there is a Ti-Zr-Cu-Ni gradient diffusion layer 2 with a thickness of 12μm between the wear-resistant block 3 and the fan blade damping boss 1. The percentage of Ti atoms at the interface decreases from the wear-resistant block 3 side to the substrate side. The gradient diffusion layer 2 contains a continuous and dense TiC reaction layer 4 and a ZrC reaction layer 4. The average particle size of the compound at the interface is 1.5μm, and the volume fraction of TiC / ZrC reaction layer 4 is 22%.

[0090] The component prepared in Example 2 has a gradient diffusion layer 2 with a thickness of 14 μm, a continuous and dense TiC / ZrC reaction layer 4 without cracks, an average particle size of 1.2 μm for the interfacial compounds, and a volume fraction of 28% for the TiC / ZrC reaction layer 4.

[0091] The component prepared in Example 3 has a gradient diffusion layer 2 with a thickness of 10 μm, a continuous TiC / ZrC reaction layer 4, an average particle size of 1.8 μm for the interfacial compounds, and a volume fraction of 19% for the TiC / ZrC reaction layer 4.

[0092] The component prepared in Example 4 has a gradient diffusion layer 2 with a thickness of 8 μm, a continuous TiC / ZrC reaction layer 4, an average particle size of 2.0 μm for the interfacial compounds, and a volume fraction of 15% for the TiC / ZrC reaction layer 4.

[0093] The component prepared in Example 5 has a gradient diffusion layer 2 with a thickness of 10 μm, a continuous TiC reaction layer 4, an average particle size of 1.9 μm for the interfacial compounds, and a volume fraction of 20% for the TiC reaction layer 4.

[0094] The component prepared in Example 6 has a gradient diffusion layer 2 with a thickness of 9 μm, a continuous TiC / ZrC reaction layer 4, an average particle size of 1.9 μm for the interfacial compounds, and a volume fraction of 17% for the TiC / ZrC reaction layer 4.

[0095] The component prepared in Example 7 has a gradient diffusion layer 2 with a thickness of 10 μm, a continuous TiC reaction layer 4, an average particle size of 1.8 μm for the interfacial compounds, and a volume fraction of 19% for the TiC reaction layer 4.

[0096] The component prepared in Example 8 has a gradient diffusion layer 2 with a thickness of 13 μm, a continuous and dense TiC / ZrC reaction layer 4, an average particle size of 1.4 μm for the interfacial compounds, and a volume fraction of 24% for the TiC / ZrC reaction layer 4.

[0097] The component prepared in Example 9 has a gradient diffusion layer 2 with a thickness of 11 μm, a continuous and dense TiC / ZrC reaction layer 4, an average particle size of 1.6 μm for the interfacial compounds, and a volume fraction of 20% for the TiC / ZrC reaction layer 4.

[0098] The results of the above nine product verification examples of the present invention all conform to the structural characteristics of the products of the present invention, namely, a gradient diffusion layer 2 thickness of 8μm~15μm, a gradient distribution of Ti elements, a continuous and dense TiC / ZrC reaction layer 4, an average particle size of the compound ≤2μm, and a reaction layer volume fraction of 15%~30%.

[0099] The present invention is compared with the method described above by the present invention through the following comparative examples: Comparative Example 1: The difference between this comparative example and Example 1 is that: in step 2, the brazing foil is prepared by the traditional vacuum melting method, with a density of 94% and a grain size of 25μm; in step 4, the traditional vacuum brazing method is used, with a heating rate of 5℃ / min and a holding time of 900℃ for 60min.

[0100] Test results: The shear strength of the weld interface is only 180 MPa, there are a large number of pores and brittle Ti2Cu phases at the interface, the gradient diffusion layer 2 is discontinuous, and the volume fraction of TiC / ZrC reaction layer 4 is only 8%, which cannot meet the installation requirements.

[0101] Comparative Example 2: The difference between this comparative example and Example 2 is that the axial pressure in step 4 is applied instantaneously (from 10MPa to 35MPa within 1 second), while the other parameters are exactly the same as in Example 2.

[0102] Test results: The shear strength of the weld interface is 260 MPa. There are 3 microcracks at the interface. The edge of the pre-sintered sheet is broken. The reason is that the instantaneous pressure caused stress concentration inside the pre-sintered sheet, which could not transmit pressure evenly.

[0103] Comparative Example 3: The difference between this comparative example and Example 1 is that the pulse frequency in step 4 is changed to 10kHz (the upper limit), while the other parameters are exactly the same as in Example 1.

[0104] Test results: The shear strength of the weld interface was 315 MPa, the thickness of the gradient diffusion layer 2 was 11 μm, the average particle size of the interface compound was 1.3 μm, and the volume fraction of the TiC / ZrC reaction layer 4 was 25%. Compared with Example 1, the high-frequency pulse refined the grains but the diffusion layer was slightly thinner, proving that the pulse frequency is a key variable affecting the interface structure, and qualified products can be obtained within the scope of this invention.

[0105] Comparative Example 4: The difference between this comparative example and Example 4 is that the welding temperature in step 4 is 700℃ and the welding time is 60min, while the other parameters are the same as in Example 4.

[0106] Test results: The shear strength of the weld interface was only 145 MPa, with a large area of ​​unwelded region at the interface. The brazing filler metal pre-sintered sheet 5 did not form a continuous liquid phase film, the gradient diffusion layer 2 was discontinuous, the TiC / ZrC reaction layer 4 had a volume fraction of only 3%, and the Co content within the surface 50 μm of the wear-resistant block 3 after welding decreased by 0.5 wt% compared to the original value. This proves that the brazing filler metal cannot form an effective liquid phase film below 750℃, and the interfacial reaction is insufficient.

[0107] Comparative Example 5: The difference between this comparative example and Example 3 is that: in step 2, the SPS sintering temperature is 680℃, the axial pressure is 20MPa, and the holding time is 1min, resulting in a brazing filler metal pre-sintered sheet 5 with a density of 93%; the parameters in step 4 are the same as in Example 3.

[0108] Test results: The shear strength of the weld interface was only 155 MPa, there was a large area of ​​unbonded area at the interface, the liquid phase film was discontinuous, the interface porosity was 3.2%, the gradient diffusion layer 2 was discontinuous, and the volume fraction of the TiC / ZrC reaction layer 4 was only 2%. This proves that when the density is below 96%, the porosity is >4%, and a functional continuous liquid phase film cannot be formed.

[0109] Comparative Example 6: The difference between this comparative example and Example 8 is that the welding time in step 4 is 60 minutes (exceeding the upper limit of 45 minutes corresponding to 850℃), while the other parameters are exactly the same as those in Example 8.

[0110] Test results: The shear strength of the weld interface was 240 MPa. After welding, the Co content within the surface 50 μm of the wear-resistant block 3 decreased by 6.2 wt% compared to the original value (>5 wt%, judged as excessive loss). Microcracks appeared at the interface. The volume fraction of TiC / ZrC reaction layer 4 in the gradient diffusion layer 2 decreased to 12%, and the average particle size of the compound increased to 2.8 μm. This demonstrates that holding at 850℃ for more than 45 min leads to excessive Co loss and coarsening of the interface structure. Although the pre-sintered sheet can form a continuous liquid phase film, the process conditions exceeded the scope defined by this invention.

[0111] The embodiments of the present invention achieve the following technical effects: 1. High interfacial bonding strength: Pulsed current diffusion welding utilizes electroplasticity and electrodiffusion effects to activate the interface to be welded, promoting pore closure and directional diffusion of elements, achieving full spreading and wetting; the brazing filler metal pre-sintered sheet prepared by spark plasma sintering has high density (96%~99.5%) and fine grains (≤5μm), and its densification is sufficient to form a continuous liquid phase film during pulsed current diffusion welding, which fully closes the interfacial micropores under axial pressure. At the same time, C generated by WC decomposition reacts in situ with Ti / Zr to generate nano-sized TiC / ZrC particles, forming a gradient diffusion layer, so that the interfacial shear strength reaches more than 265MPa, which is significantly better than the 180MPa level of traditional brazing.

[0112] 2. Minimal thermal damage and excellent performance of the wear-resistant block: Compared to traditional processes, pulsed current diffusion welding can achieve a heating rate of 100℃ / min~200℃ / min, significantly shortening the welding time and reducing the thermal impact on the base material, effectively minimizing the loss of the Co binder phase in WC-Co cemented carbide. In the preferred embodiment, the Co content within the surface 50μm of the wear-resistant block after welding decreases by no more than 2.1wt% compared to the original value; in all other embodiments, this value does not exceed 5wt%, indicating that the process conditions of the present invention cause minimal thermal damage to the wear-resistant block, maintaining its original hardness and toughness and extending the service life of the wear-resistant layer.

[0113] 3. Clear process window and strong adaptability: Through extensive experimental verification, this invention has established a wide process window of 750℃~950℃ / 20min~90min and a wide density range of 96%~99.5%, as well as the negative correlation between welding temperature and welding time. A clear preferred range of 30min~45min is given at the 850℃ inflection point. By adjusting the brazing filler metal system and welding parameters, it can be adapted to fan blade damping bosses of different sizes and materials. It is especially suitable for large-size wear-resistant blocks and temperature-sensitive lightweight substrates, and has broad engineering application prospects.

[0114] 4. The product has stable performance and detectable structural features: the thickness of the gradient diffusion layer at the interface of the obtained component is controlled at 8μm~15μm, the average particle size of the compound is ≤2μm, the structure is uniform and dense, and there are no cracks or pores; the present invention also provides clear and feasible detection methods for each structural feature, which is convenient for third-party verification and rights protection evidence.

[0115] 5. Simplified process and good consistency: The use of prefabricated wear-resistant blocks and pre-sintered sheets to replace manual mixing and coating avoids the 16-24 hour shelf life limitation after the brazing filler metal and wear-resistant particles are mixed, reduces the dependence on the operator's skill level, facilitates standardized and refined mass production, and can be extended to rapid repair applications in the field of aero-engines.

[0116] Obviously, those skilled in the art should understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Various modifications and variations of the embodiments of the present invention are possible for those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a wear-resistant layer assembly for a fan blade damping boss using pulsed current diffusion welding, characterized in that, include: WC-Co cemented carbide is machined into wear-resistant blocks that are compatible with the working surface of the fan blade damping boss. Titanium-based brazing filler metal powder is pressed into brazing filler metal pre-sintered sheets using spark plasma sintering technology. The densification degree of the brazing filler metal pre-sintered sheets is sufficient to form a continuous liquid phase film during subsequent pulsed current diffusion welding. The brazing filler metal pre-sintered sheets are stacked between the working surface of the fan blade damping boss and the wear-resistant block and fixed to form a component to be welded. The component to be welded is placed in a pulsed current diffusion welding device, and pulsed current diffusion welding is performed under the process conditions that make the brazing filler metal pre-sintered sheet form a continuous liquid phase film. This allows the wear-resistant block to achieve metallurgical bonding with the fan blade damping boss through the brazing filler metal pre-sintered sheet, resulting in a fan blade damping boss wear-resistant layer component.

2. The pulsed current diffusion welding preparation method according to claim 1, characterized in that, The titanium-based solder powder is Ti-Zr-Cu-Ni or Ti-Cu-Ni, and the density of the solder pre-sintered sheet is 96%~99.5%.

3. The pulsed current diffusion welding preparation method according to claim 2, characterized in that, The pre-sintered brazing filler metal sheet has a density of ≥98% and an average grain size of ≤5μm.

4. The pulsed current diffusion welding preparation method according to any one of claims 1 to 3, characterized in that, The temperature for spark plasma sintering is 750℃~850℃, the axial pressure is 30MPa~50MPa, and the holding time is 3min~10min.

5. The pulsed current diffusion welding preparation method according to claim 1, characterized in that, The process conditions satisfy any combination of the following: (1) The welding temperature is 750℃~850℃ and the welding time is 30min~90min; (2) The welding temperature is 850℃~950℃, and the welding time is 20min~45min; The welding temperature is negatively correlated with the welding time, and the welding time is 30 min to 45 min at 850℃.

6. The pulsed current diffusion welding preparation method according to claim 1, characterized in that, The WC-Co cemented carbide is WC-10Co or WC-12Co, the thickness of the wear-resistant block is 500μm~1000μm, and the surface roughness Ra of the mating surface is ≤0.4μm.

7. The pulsed current diffusion welding preparation method according to claim 1, characterized in that, The thickness of the pre-sintered brazing filler metal sheet is 50μm~250μm, the area is not less than the contact surface area of ​​the wear-resistant block, and the difference in thermal expansion coefficient between it and that of WC-Co cemented carbide is ≤2×10. -6 / ℃.

8. A fan blade vibration damping boss wear-resistant layer assembly, characterized in that, The material is prepared by the pulsed current diffusion welding method according to any one of claims 1-7; a gradient diffusion layer with a thickness of 8μm~15μm is provided between the wear-resistant block and the damping boss of the fan blade, the Ti element at the interface is distributed in a decreasing gradient, and the material contains a continuous and dense TiC and / or ZrC reaction layer, the average particle size of the compound is ≤2μm, and the interfacial shear strength of the gradient diffusion layer is ≥265MPa.

9. The fan blade damping boss wear-resistant layer assembly according to claim 8, characterized in that, The volume fraction of TiC and / or ZrC reaction layer in the gradient diffusion layer is 15% to 30%.

10. The fan blade damping boss wear-resistant layer assembly according to claim 8, characterized in that, The interfacial shear strength of the gradient diffusion layer is ≥265MPa, and the Co content within 50μm of the surface layer of the wear-resistant block after welding is reduced by no more than 5wt% compared to the original value.